Digital Entrepreneurship Training for Madrasah Students through a Community Service Program - Arnolt Kristian Pakpahan; Gatri Lunarindiah; Febria Nalurita; Danang Islami; Aziza Idris Kurniawan (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
This Community Service (PkM) program aims to enhance students’ understanding and skills in digital entrepreneurship at Madrasah Aliyah Negeri (MAN) 3 Central Jakarta. The program was initiated due to students’ limited ability to integrate digital technology into modern entrepreneurial concepts, particularly in product innovation, promotion, and online business management. The implementation method adopted a participatory approach involving workshops, practical simulations, digital marketing training, and direct mentoring in creating social media promotional content. The activity emphasized a learning by doing model, enabling students not only to understand theoretical concepts but also to apply them in real situations. The results show significant improvements in students’ ability to utilize digital platforms such as Instagram Business, Canva, and WhatsApp Business for school-based entrepreneurship projects. Students demonstrated higher creativity in product branding, content creation, and teamwork collaboration. This program effectively nurtured digital entrepreneurial mindsets and adaptive technological behavior, thereby strengthening students’ readiness to face future challenges in the digital economy.